ANALYSIS OF MATHEMATICAL PROBLEM SOLVING ABILITY OF CLASS VII STUDENTS SMP IT MUTIARA GLOBAL ON SOCIAL ARITHMETIC MATERIALS - Wiwik Julia Fitri; Kartini Kartini (Jurnal Pendidikan Matematika dan IPA)
The purpose of this research is to describe student’s mathematical problem solving abilities, especially in social arithmetic material uses descriptive research method. This research uses descriptive method. The subjects were class VII students of SMP IT Mutiara Global Pekanbaru as many as 15 even semester students for the 2020/2021 academic year. Written instruments test of KPMM with 3 questions and 4 aspects of KPMM according to Polya were used in this research. From this research, the average indicator of understanding the problem is 91.85%, planning solution is 51.11%, completing solution plan is 75.55%, and interpreting the results is 37.78%. Student’s KPMM of SMP IT Mutiara Global Pekanbaru class VII are included in medium criteria with an average value of 64.07%. The results of research showed that students have not experienced working on non-routine questions (different), and need to be accustomed to working on non-routine questions to train students' KPMM.